The combined effect of bioactive glass and platelet-rich fibrin in treating human periodontal intrabony defects - A clinicoradiographic study - Deepshika Saravanan; Saravanan Rethinam; Kavitha Muthu; Ambika Thangapandian (Wolters Kluwer Medknow Publications, 2019)
Background: Platelets are richest source for cytokine and growth factors which are two important components for the re-establishment of bone and maturation of the soft tissue. Aims and Objective: The additive effect of PRF along with a synthetic bone graft material in treating human intrabony periodontal defects has been evaluated in this study. The appropriate use of platelet-rich fibrin (PRF) as an alternate comfortable graft material to restore the lost periodontal tissues has been well documented and has given clinically promising outcome. Materials and Method: Platelet-rich fibrin (PRF) is prepared from patient's own blood which is autologous in nature. Perio Glas (PG) is an easy to use synthetic absorbable osteostimulative as well as osteoconductive bone graft material. The selected 30 sites were randomly divided into two groups such as Test (15 sites using PRF) and Control (15 sites without PRF). Results: At the end of Six months, the post-operative evaluations revealed significant reduction in PPD and gain in CAL. Radiographic evidence of bone formation was also noticed. The incorporation of PRF with synthetic bone graft (perioglas) produces effective and rapid periodontal regeneration with improved healing in intrabony osseous defects. The PRF group showed a mean Radiographic Defect Fill (RDL) of 1.24 ± 0.04 compared with 0.79 ± 0.07 of control group which is statistically significant. Conclusion: This combination technique can be used as an alternate grafting modality for the treatment of intrabony periodontal defects with satisfactory clinical consequences.